INVESTIGATING STRUCTURAL DIFFICULTIES IN PORTAL STEEL FRAME BUILDING - Clarke, Robert; Turner, Emily (Ayden International Journal of Basic and Applied Sciences, 2024)
The utilization of inclined beams in portal steel frame construction plays a crucial role in enhancing overall stability, reducing the need for extensive foundational materials, and achieving cost-effective solutions. The lightweight nature of the steel structure significantly contributes to its favorable seismic performance, making it a popular choice in single-storey house construction. This approach not only ensures efficient construction but also enables cost control. Portal steel frames are increasingly being employed in the construction of industrial plants due to their economic advantages. To further expand their applicability, it becomes essential to conduct a targeted analysis of design-related challenges and continuously enhance the quality of the design process